2009
DOI: 10.1007/s11814-009-0110-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and catalytic activity of H5PMo10V2O40 immobilized on nitrogen-containing mesoporous carbon (PMo10V2/N-MC) for selective conversion of methanol to dimethoxymethane

Abstract: Nitrogen-containing mesoporous carbon (N-MC) was synthesized by a templating method using SBA-15 and polypyrrole as a templating agent and a carbon precursor, respectively. The N-MC was then modified to have a positive charge, and thus, to provide a site for the immobilization of [PMo 10 V 2 O 40 ] 5− . By taking advantage of the overall negative charge of [PMo 10 V 2 O 40 ] 5− , H 5 PMo 10 V 2 O 40 (PMo 10 V 2 ) catalyst was chemically immobilized on the N-MC support as a charge-matching component. Characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…% nitrogen in N–C-1000 is not effective in reducing the acid activity, contrary to common belief that a small amount of nitrogen doped in carbon would significantly affect the support–HPA interaction. This has not been noted in previous literature, because most researchers have used unsupported HPAs as a benchmark to compare their catalysts. , Supports with higher nitrogen content (N–C-600 and mpgC 3 N 4 ), which have not been studied as supports for POMs before, produced much lower DME formation rate, regardless of coverage levels. mpgC 3 N 4 suppressed almost all of the acid activity to 2–3 orders of magnitude below that of C and N–C-1000.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…% nitrogen in N–C-1000 is not effective in reducing the acid activity, contrary to common belief that a small amount of nitrogen doped in carbon would significantly affect the support–HPA interaction. This has not been noted in previous literature, because most researchers have used unsupported HPAs as a benchmark to compare their catalysts. , Supports with higher nitrogen content (N–C-600 and mpgC 3 N 4 ), which have not been studied as supports for POMs before, produced much lower DME formation rate, regardless of coverage levels. mpgC 3 N 4 suppressed almost all of the acid activity to 2–3 orders of magnitude below that of C and N–C-1000.…”
Section: Discussionmentioning
confidence: 93%
“…Although some oxide supports have been reported to decompose HPAs, because of their basicity, there are successful cases in which intact HPAs are preserved on, for example, nitrogen-containing carbon supports. Amine-decorated carbon (N content = 1.7 wt % and 1.1 wt %), and carbon embedded with other N-containing species (e.g., pyridinic, graphitic nitrogen) (N content = 2 wt %, , 3.6 wt %, and 10.6 wt %) and nitrogen-containing polymers such as polyaniline (N content = 15 wt %) have been used as supports for HPAs. They have proven useful in isopropanol oxidation, ,,, methacrolein oxidation, methanol oxidation, and isopropanol decomposition, displaying, in all cases, a decrease in acid catalytic activity and enhanced oxidation activity, compared to unsupported HPAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al reported the same effect for SBA-15-supported H 3 PMo 12 O 40 . Kim et al explored N-doped mesoporous carbon as support to immobilize H 5 PMo 10 V 2 O 40 . DMM selectivity remained at medium level (50%) probably due to nonoptimized acidic and redox properties.…”
Section: Direct Synthesis Of Dmm Via Methanol Oxidationmentioning
confidence: 87%
“…While most studies for the direct synthesis of OME 1 were carried by means of the commonly available supports such as TiO 2 , N-doped mesoporous carbon was tested as a support. [44] However, the conclusion was not convinced due to the lack of comparable studies using carbon supports.…”
Section: -130°cmentioning
confidence: 99%